Formation of La-containing microcrystals in KCl and NaCl matrices - Demkiv, T.; Vistovskyy, V.; Savchyn, P.; Stryganyuk, G.; Voloshinovskii, A.; Demkiv, L. (Functional Materials, 2009)
The mechanism of the K₂LaCl₅ and LaCl₃ aggregate formation in KCl and NaCl matrices as a result of long-term annealing is discussed. Thermodynamic analysis of formation conditions of such aggregates has been performed. The influence of diffusion processes and the elastic deformation of aggregates by the matrix are considered. It has been shown that Ce and Pr as activator ions penetrate efficiently into aggregates.